Optimizing Collaborative Quality Improvement Strategies to Decrease Neonatal Asphyxia Incidence: A Scoping Review - Andreas Syabrullah; Herin Mawarti; Masruroh Hasyim (Journal Research of Social Science, Economics, and Management, 2025)
Neonatal asphyxia remains a leading cause of neonatal mortality, particularly in low- and middle-income countries (LMICs). Quality Improvement Collaboratives (QICs) have emerged as a structured approach to bridge the gap between evidence-based interventions and clinical practice in neonatal care. This scoping review aimed to systematically map the characteristics, core components, and reported outcomes of QIC frameworks implemented to reduce the incidence of neonatal asphyxia. The review was conducted following the Arksey and O’Malley framework and PRISMA-ScR guidelines. A systematic search of seven electronic databases (2016–2025) identified seven eligible studies. Data on QIC components, implementation strategies, and outcomes were extracted and synthesized. The findings indicate that QICs, often incorporating Plan-Do-Study-Act cycles, mentorship, and audit-feedback, were implemented across various LMICs. Core components included interprofessional collaboration, protocol standardization, and real-time data monitoring. Enabling factors such as leadership engagement and effective communication enhanced adherence to care protocols, while workforce shortages and inadequate infrastructure posed barriers. The reviewed studies consistently reported improvements in clinical practices and reductions in neonatal asphyxia or related mortality. QICs are effective in improving neonatal outcomes through structured, team-oriented approaches. For long-term sustainability, they must be integrated into broader health system strengthening initiatives, addressing systemic barriers and securing institutional support.